A nonlinear modified CONVEF-AD based approach for low-dose sinogram restoration - Tiwari S.; Srivastava R.; Arya K.V. (My University, 2025)
Preprocessing the noisy sinogram before reconstruction is an effective and efficient way to solve the low-dose X-ray computed tomography (CT) problem. The objective of this paper is to develop a low-dose CT image reconstruction method based on statistical sonogram smoothing approach. The proposed method is casted into a variational framework and the solution of the method is based on minimization of energy functional. The solution of the method consists of two terms, viz., data fidelity term and a regularization term. The data fidelity term is obtained by minimizing the negative log likelihood of the signal-dependent Gaussian probability distribution which depicts the noise distribution in low-dose X-ray CT. The second term, i.e., regularization term is a nonlinear CONvolutional Virtual Electric Field Anisotropic Diffusion (CONVEF-AD) based filter which is an extension of Perona–Malik (P–M) anisotropic diffusion filter. The main task of regularization function is to address the issue of ill-posedness of the solution of the first term. The proposed method is capable of dealing with both signal-dependent and signal-independent Gaussian noise, i.e., mixed noise. For experimentation purpose, two different sinograms generated from test phantom images are used. The performance of the proposed method is compared with that of existing methods. The obtained results show that the proposed method outperforms many recent approaches and is capable of removing the mixed noise in low-dose X-ray CT. © Springer Science+Business Media Singapore 2017.